Community and Species-Level Changes of Insect Species Visiting Mangifera indica Flowers Following Hurricane María: “The Devil Is in the Details” - Cabrera-Asencio, Irma; Meléndez-Ackerman, Elvia J. (Frontiers in Ecology and Evolution, 2021)
Mangifera indica is a widespread economically important tropical fruit. An ongoing study at the Juana Diaz Experimental Station in Puerto Rico aims to understand the factors that influence local pollination success and fruit yields in four fields each hosting a different mango cultivar (Keitt, Kent, Tommy Atkins, and Julie) at different temporal scales. Here we describe the results of insect collection campaigns that evaluated flower visitor communities of these fields (from January to April) in the seasons of 2017 (before Hurricane Maria), 2018 (after Hurricane Maria) and 2019 (2 years after Hurricane Maria). We expected a reduction in diversity, abundance and yields and even changes in composition following the hurricane events of 2017. Over the 3 years, plants were visited by a combined total of 50 insect species, mostly Diptera (also the most abundant), Hymenoptera, Coleoptera, and Lepidoptera. The relative abundances of insect communities changed but overall species richness of insect communities appeared to be recovering by 2019. A clear decline in overall crop yields for two of the four fields (hosting Kent and Tommy Atkins) was seen in 2018 but then recovered in one and surpassed pre-hurricane levels in another in 2019. Mango trees experienced an increase in the abundance for all insect groups in 2019 following the 2018 decline and only one field (hosting Kent) experienced significant species richness declines in 2018. Two of the most dominant insects, Palpada vinetorum (Diptera) and Apis mellifera (Hymenoptera), showed a “reduction-recovery” pattern for the period of 2018–2019 but not so for Cochliomyia minina which was very abundant in 2018 in three out of four cultivars but then returned to pre-hurricane levels in 2019. In 2017, the trees exposed to higher richness and abundance of species experienced higher yields regardless of cultivars but these relationships when present were often weaker in 2018 (post-hurricane) and 2019 and not all cultivars were equally successful at attracting the same levels of diversity and abundance of insects. Our results do support the importance of pollinator diversity and abundance to improve agricultural yields. They also emphasize that within the context of future extreme atmospheric events, that there needs to be an understanding of not only how these pollinator communities may recover from these events but also of how individual pollinators (vs. other factors) may influence plant yields to develop informed management strategies following such events.